2013
DOI: 10.3233/rnn-120289
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic umbilical cord blood therapy combined with erythropoietin for patients with severe traumatic brain injury: Three case reports

Abstract: Objective: To report the safety and efficacy of a novel therapeutic trial with umbilical cord blood (UCB) and concomitant recombinant human erythropoietin (rhEPO), which was tried for three cases of severe traumatic brain injury (TBI) in rehabilitation. Design: Case series. Setting: University hospital setting. Participants: Three patients with TBI over 6-months post-injury. Interventions: Intravascular administration of allogenic UCB and injection of rhEPO, and rehabilitation therapy. Outcomes: For safety, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In this context, numerous studies have shown neuroprotective effects of MNC hUCB administered into animal models of ALS, AD, Parkinson's disease, ischaemic stroke and traumatic brain injury . However, insignificant numbers of MNC hUCB were detected in the CNS of these animal models after intravenous cell administration.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, numerous studies have shown neuroprotective effects of MNC hUCB administered into animal models of ALS, AD, Parkinson's disease, ischaemic stroke and traumatic brain injury . However, insignificant numbers of MNC hUCB were detected in the CNS of these animal models after intravenous cell administration.…”
Section: Discussionmentioning
confidence: 99%
“…Human UCB containing citrate phosphate dextrose adenine as an anticoagulant was provided from the cord blood bank of CHA Medical Center. Informed by previous clinical trials (27), we injected a total of 3 × 10 7 kg nucleated cells. This experiment was approved by the Institutional Ethics Committee of CHA Bundang Medical Center, Korea.…”
Section: Methodsmentioning
confidence: 99%
“…The number of total nucleated cells of hUCBC used in treatment was based on our previous clinical trial which was performed in patients with traumatic brain injury (27). Furthermore, the dosage of EPO was selected based on a corresponding dose in a clinical trial for cerebral palsy (28) that is considered safe for humans.…”
Section: Methodsmentioning
confidence: 99%
“…The most common neurological condition studied was cerebral palsy [18,20,24À26,28]. The remaining studies targeted autism spectrum disorder [22]; stroke [21]; traumatic brain injury [19]; or a mixture of conditions, including neurological (>59% recruited with a neurological condition [27]. All participant data from Vyas et al [27] were included in the results, regardless of condition.…”
Section: Participants Targeted Conditions and Types Of Studies Includedmentioning
confidence: 99%